Sore throat in primary care project: a clinical score to diagnose viral sore throat - Mistik, Selcuk (Fam Pract, 2015)
OBJECTIVE. Viral agents cause the majority of sore throats. However, there is not currently a score to diagnose viral sore throat. The aims of this study were (i) to find the rate of bacterial and viral causes, (ii) to show the seasonal variations and (iii) to form a new scoring system to diagnose viral sore throat. METHODS. A throat culture for group A beta haemolytic streptococci (GABHS) and a nasopharyngeal swab to detect 16 respiratory viruses were obtained from each patient. Over a period of 52 weeks, a total of 624 throat cultures and polymerase chain reaction analyses were performed. Logistic regression analysis was performed to find the clinical score. RESULTS. Viral infection was found in 277 patients (44.3%), and GABHS infection was found in 116 patients (18.5%). An infectious cause was found in 356 patients (57.1%). Rhinovirus was the most commonly detected infectious agent overall (highest in November, 34.5%), and the highest GABHS rate was in November (32.7%). Analysis of data provided a scoring system, called the Mistik Score, to diagnose viral sore throat. The predictive model for positive viral analysis included the following variables: absence of headache, stuffy nose, sneezing, temperature of ≥37.5°C on physical examination, and the absence of tonsillar exudate and/or swelling. The probability of a positive viral analysis for a score of 5 was 82.1%. CONCLUSION. The Mistik Score may be useful to diagnose viral sore throat. We suggest its use either alone or in combination with the Modified Centor Score.